The methanolic extract of Byrsonima intermedia mitigates colonic injury in experimental colitis through redox restoration, cytokine modulation, and tissue repair - Karla Stella Figueiredo Romano; Felipe Leonardo Fagundes; Quélita Cristina Pereira; Maycon Tavares Emílio-Silva; Larissa Lucena Périco; Vinicius Peixoto Rodrigues; Gabriela Bueno; Mateus Magami Yoshitani; Giovana Pacciulli Pereira; José Aires Pereira; Carlos Augusto Real Martinez; Alessandra Gambero; et al. (Inflammopharmacology, 2026)
This study evaluated the anti-inflammatory and antioxidant effects of a methanolic extract of Byrsonima intermedia leaves (EBi) in a rat model of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis. Male Wistar rats received intracolonic TNBS for lesion induction and relapse, followed by oral treatment with EBi for seven days. EBi markedly reduced the severity of colonic injury, as demonstrated by a 63% decrease in macroscopic damage, along with reductions in inflammatory infiltrate (32%) and neutrophil accumulation (52%) compared to the vehicle group. These protective effects were accompanied by significant attenuation of myeloperoxidase (MPO) activity and lipid peroxidation, together with increased superoxide dismutase (SOD) activity and glutathione levels (GSH), indicating restoration of redox homeostasis. EBi also modulated key inflammatory mediators, promoting IL-10 upregulation while downregulating IL-1 β , MCP-1, and TLR4 expression in colonic tissue. Histological analysis confirmed substantial improvement in tissue architecture and inflammatory status. Collectively, these findings demonstrate that B. intermedia exerts multi-target anti-inflammatory and antioxidant actions that contribute to tissue repair in experimental colitis, supporting its potential as a promising natural therapeutic candidate for inflammatory bowel disease. Graphical abstract Multi-target mechanisms underlying the protective effects of Byrsonima intermedia in experimental TNBS-induced colitis. The extract reduces macroscopic lesions, restores redox homeostasis (↑SOD, ↑GSH, ↓MDA, ↓ROS), and modulates key inflammatory mediators (↓IL-1 β , ↓MPO, ↓MCP-1, ↑IL-10), collectively promoting tissue repair and attenuation of intestinal inflammation . Created in BioRender. Pereira, Q. (2025)